Comparative effects of three 48-week community-based physical activity and exercise interventions on aerobic capacity, total cholesterol and mean arterial blood pressure. Issue 1 (30th March 2016) - Mann, Steven; Jimenez, Alfonso; Domone, Sarah; Beedie, Chris
Abstract : Aim: Insufficient research examines the treatment effectiveness of real-world physical activity (PA) interventions. Purpose: We investigated the effects of 3 interventions on directly measured cardiovascular variables. All treatments and measures were administered in community settings by fitness centre staff. Methods: Participants were sedentary individuals receiving no medication to reduce cardiovascular disease (CVD) risk (n=369, age 43 ±5 years). In a semirandomised design, participants were allocated to a structured gym exercise programme (STRUC), unstructured gym exercise (FREE), physical activity counselling (PAC) or a measurement-only control condition (CONT). Measures were: predicted aerobic capacity (VO2 : mL kg min), mean arterial blood pressure (MAP: mm Hg) and total cholesterol (TC: mmol/L), and were taken at baseline and 48 weeks. Results: Data analysis indicated a statistically significant deterioration in TC in CONT (0.8%, SD=0.5, p=0.005), and a statistically significant improvement in MAP in STRUC (2.5%, SD=8.3, p=0.004). Following a median split by baseline VO2, paired-sample t tests indicated significant improvements in VO2 among low-fit participants in STRUC (3.5%, SD=4.8, p=0.003), PAC (3.3%, SD=7.7, p=0.050) and FREE (2.6%, SD=4.8, p=0.006), and significant deterioration of VO2 among high-fit participants in FREE (−2.0%, SD=5.6, p=0.037), and PAC (−3.2%, SD=6.4, p=0.031). Conclusions: Several forms of PA may offset increased cholesterol resulting from inactivity. Structured PA (exercise) might be more effective than either unstructured PA or counselling in improving blood pressure, and community-based PA interventions might be more effective in improving VO2 among low-fit than among high-fit participants.